The Role of Islamic Religious Education Teachers in Shaping Students’ Religious Awareness in the Digital Era at SMAN 1 Tenggarong - Aisya Salsabila; Trisno Sutrisno; Ridho Arka Putra Utama; Gadis Ramadayanti; Cantika Amanda Putri Nabilla; Mukmin Mukmin; Sobirin Sobirin; Rina Malini (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2026)
This study aims to analyze the role of Islamic Religious Education (PAI) teachers in fostering students’ religious awareness in the digital era at SMAN 1 Tenggarong. The research employed a descriptive qualitative approach using in-depth interviews, observation, and documentation as data collection techniques. The findings reveal that students’ religious awareness is influenced by both internal and external factors, including self-motivation, family environment, peer influence, and digital media exposure. In the digital era, PAI teachers play important roles not only as educators, but also as mentors, motivators, role models, and filters of religious information accessed by students through digital media. Effective strategies implemented by teachers include religious habituation, emotional and contextual approaches, and the selective use of technology. The study concludes that collaboration among teachers, families, and schools is essential in creating a religious environment that supports the development of students’ religious awareness in the digital era.